Thermal Thinning of Magnetorheological Fluid and its effect on MR brake performance (International Journal of Current Engineering and Technology, 2015)
The aim of this paper is review the viscosity of magnetorheological (MR) fluid as function of temperature. A rheological model of shear stress dependent on temperature has been established. MR fluid has been characterized at various temperatures for different magnetic fields to observe the thermal thinning of MR fluid. In order to confirm the thermal thinning behavior of MR fluids, experiments have been conducted in MR brake test rig. The results show that with increase in temperature, there is decrease in braking torque.
Keywords: MR fluid; MR brake; Thermal Thinning.